The Psychological Construction of Racial Superiority in James Weldon Johnson’s The Autobiography of an Ex-Coloured Man - Geoffroy Junior Aka N’goran AMAN (Ziglôbitha, 2023)
Abstract: This article analyses the psychological construction of racial superiority in The Autobiography of an Ex-Coloured Man. It shows how white characters psychologically succeed in professing and claiming superiority over black characters. Psychoanalysis, the literary theory used for our analyses, enabled us to find out that white characters focus on unfounded racial considerations such as prejudices, stereotypes and racial slurs to make colored people feel inferior by denying them of any qualities and values. This psychological mechanism leads them to express a complex of superiority over Blacks. Such a situation automatically results in Blacks’ complex of inferiority, which is noticeable through their self-hatred, a loss of their self-esteem and a strong long for white identity. These antithetic complexes have an impact on the way skin colour is perceived by people in society. In the collective consciousness, white skin and black skin are diametrically opposed in terms of social meaning. On the one hand, people unconsciously associate values, rights, qualities, power and privileges to white skin. On the other hand, they associate black skin colour with subordination, worthlessness and powerlessness. Keywords: complex, inferiority, psychology, race, superiority